Pengaruh Pemberian Minyak Atsiri Daun Kemangi (Ocimum americanum L.) Terhadap Motilitas Usus Mencit Putih Jantan - Sriyani, Dewi; Saputri, Fadlina Chany (UI Scholars Hub, 2016)
Kemangi (Ocimum americanum L.) is a well known plant that contains essential oils with citral as a major compound. Citral is reported to have beneficial effect on intestinal motility. In the present study, we investigated the effect of essential oil of kemangi leaves (Ocimum americanum L.) on male DDY mices intestinal motility. Thirty mices were divided into six groups and each group was pretreated with 0,2 ml of 0,5% CMC (negative control), 1 mg/kg BW of atropine sulfate (positive control), 5 mg/kg BW of citral (comparative control), and three dose variation of volatile oil of kemangi leaves (25 mg/kg BW; 50 mg/kg BW; 100 mg/kg BW) orally. All mices were given charcoal meal suspension 0,2 ml orally, and the animals were sacrificed. The percentage ratio and inhibition were analysed by measure the intestinal transit of charcoal. The results showed that the essential oil of kemangi leaves dose 100 mg/kg BW significantly (p < 0.05) reduced intestinal transit in mice with the percentage ihibition value of 59,79%. This value is not significant different (p > 0.05) compared with citral and atropine sulfate. It is concluded that the essential oil of kemangi leaves has potential effect as antispasmodic agent.